Working Time Allocation of Rice Farmer Households Based on Gender Dimensionof Batak Toba Culture at Toba Samosir North Sumatera - Ulfa Nadra; Purbayu Budi Santosa; Hadi Sasana (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
This research aims to analyze: time allocation and type of women farmer’s working and men farmer’s working in rice farming and factors that influence on time allocation of women farmer’s working. This research was done in Balige District, Laguboti District and Porsea District on Toba Samosir Regency at North Sumatera Province. The reasons of making these districts as a choice are: peoples of these districts are working as a rice farmers and the location of these districts are easier to reach. This research use purposive sampling with 99 rice-farmers households on Toba Samosir Regency as samples.Time allocation of women farmers on rice-farming in Toba Samosir Regency is longer than men farmers. From the regression test on variabels that influence with time allocation of women farmers are the education of women farmers, the education of men farmers,the men farmers’ period of staying on another town and Batak Culture significantly influence in level of confidence 95%. This research recommended that agricultural development still needs to repair by using local wisdom or local culture. It can creates local community that concern about gender equality, so it can increase working-time allocation and increase farm working-quality to create the wealth farmer households and increase the GDP of Toba Samosir Regency on North Sumatera Province. Keywords: gender, North Sumatera, rice farmer,time allocation, Toba Samosir